Sexually risky behaviors in patients with bipolar disorder and heroine dependence: a comparative study - Karadağ, Figen; Gürsu Hariri, Aytül; Eşsizoğlu, Altan (Journal of Dependence, 2004)
Objective: This study aims to determine and compare the sexually risky behaviour of patients with bipolar disorder and heroine addiction. Method: This study consists of 80 patients with bipolar disorder and 138 patients with heroine addiction. All patients were given a socio-demographic data form and a semistructured form on sexually risky behaviour, prepared by the authors. Results: Patients with heroin dependence had started taking drug at an earlier age and they had a longer disease course. The number of partners they changed was significantly higher and their partners were also polygamous, they had more relationships with prostitutes. They established more relationships with individuals who had sexually transmitted diseases or were IV drug users. They had participated more in group sex activities and had contacted more sexually transmitted diseases. Anti HCV was found positive in 36.6% and AntiHBs was positive in 16.1% of the patients with heroine dependence. Men had a higher sexual intercourse frequency and changed more partners. They had more sexual intercourses under drug influence and, they had more sexually transmitted diseases. Conclusion: Both groups exhibited sexually risky behaviour; however, patients with heroine addiction had more risk taking behaviour. Training such patients on sexually risky behaviour will diminish the damages with respect to both themselves and the society.